PERANCANGAN KAWASAN SIRKUIT BALAP 150CC PONTIANAK - Handalan, Najmi Zahir; Affrilyno, Affrilyno; Nurhamsyah, Muhammad (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Motorsports in Indonesia are growing. This is proven by the increasing number of areas with permanent and/or non-permanent racing circuits with improvements on existing ones. The Sultan Syarif Abdurrahman Pontianak racing circuit was closed since 29 October 2020 until an undetermined time. West Kalimantan and Pontianak City require racing circuits with national standards and adequate facilities. The author's Design of the Pontianak 150cc Racing Circuit Area tries to answer the required racing circuit. The author studied the racing circuit standards which are referenced by IMI, FIM and CIK-FIA also the precedents of racing circuits and race events. An analysis conducted related to the design subject and the facility needs of a racing circuit. The author determines which sites around the city of Pontianak with an adequate area. The design refers to the needs of the 150cc class race which is often held in West Kalimantan Province. The design's concept is arena concept. The design has pit building, medical building and visitor/audience buildings which are placed around the racetrack. With the learning outcomes of circuit standards, circuit precedents and racing event precedents, the design concept can be the beginning of a racing circuit construction needed by West Kalimantan and Pontianak City.